FEATURES OF ECONOMIC DEVELOPMENT AND MONETARY POLICY OF SINGAPORE - Maysigova, L.A.; Niyazbekova, Sh.U.; Bunevich, K.G.; Saiymova, M.D.; Blazhevich, O.G.; Issayeva, B.K.; Rey, I.Yu. (Scientific Journal of Pedagogy and Economics, 2020)
The relevance of the topic of this study is due to the fact that the balance of payments is a reflection of the economic condition of the country, as well as a document that covers the entire range of operations of the country in the foreign economic sphere. Based on the analysis of modern publications, it is determined that the phenomenon of Singapore causes wide scientific and practical interest of both scientists and practitioners. In the article, the authors identified a number of factors that have the most significant impact on the country’s monetary policy. The stages of development of the monetary policy of Singapore are systematized. The authors conducted a study of the dynamics of foreign trade in Singapore, analyzed the composition and structure of imported and exported goods. Based on the analysis of the structure of the balance of payments of Singapore, an assessment is given of the volumes of capital inflows and outflows. According to the results of this study, the authors noted obstacles to the economic growth of Singapore, including a high dependence on exports; reduction in the working–age population; digitalization in the financial sector. In order to avoid the negative consequences, the growth factors of the main sectors of the Singapore economy were determined. The above factors make it possible to compensate for the negative aspects of this economic model, increase the competitiveness of goods and services and lead to the sustainable development of the main sectors of the Singapore economy for the long term.